Early glial activation, synaptic changes and axonal pathology in the thalamocortical system of Niemann-Pick type C1 mice. - Pressey, SN; Smith, D; Wong, A; Platt, F; Cooper, J (2012)
Niemann-Pick disease type C (NPC) is an inherited lysosomal storage disease characterised by accumulation of cholesterol and glycosphingolipids. NPC patients suffer a progressive neurodegenerative phenotype presenting with motor dysfunction, mental retardation and cognitive decline. To examine the onset and progression of neuropathological insults in NPC we have systematically examined the CNS of a mouse model of NPC1 (Npc1(-/-) mice) at different stages of the disease course. This revealed a specific spatial and temporal pattern of neuropathology in Npc1(-/-) mice, highlighting that sensory thalamic pathways are particularly vulnerable to loss of NPC1 resulting in neurodegeneration in Npc1(-/-) mice. Examination of markers of astrocytosis and microglial activation revealed a particularly pronounced reactive gliosis in the thalamus early in the disease, which subsequently also occurred in interconnected cortical laminae at later ages. Our examination of the precise staging of events demonstrate that the relationship between glia and neurons varies between brain regions in Npc1(-/-) mice, suggesting that the cues causing glial reactivity may differ between brain regions. In addition, aggregations of pre-synaptic markers are apparent in white matter tracts and the thalamus and are likely to be formed within axonal spheroids. Our data provide a new perspective, revealing a number of events that occur prior to and alongside neuron loss and highlighting that these occur in a pathway dependent manner.